2023
DOI: 10.1007/s00477-022-02362-4
|View full text |Cite
|
Sign up to set email alerts
|

Changes in NO2 and O3 levels due to the pandemic lockdown in the industrial cities of Tehran and Arak, Iran using Sentinel 5P images, Google Earth Engine (GEE) and statistical analysis

Abstract: Air pollution has very damaging effects on human health. In recent years the Coronavirus disease (COVID-19) pandemic has created a worldwide economic disaster. Although the consequences of the COVID-19 lockdowns have had severe effects on economic and social conditions, these lockdowns also have also left beneficial effects on improving air quality and the environment. This research investigated the impact of the COVID-19 lockdown on NO2 and O3 pollutants changes in the industrial and polluted cities of Arak a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 48 publications
0
1
0
Order By: Relevance
“…In comparison to the Fatala River Basin, these concentrations were approximately 25 times higher in Tehran in 2019 and 40 times higher in Arak in 2019. Comparing the data reported by Gharibvand et al [66] for Iranian cities in 2019 and 2020, it can be observed that ozone concentrations are 1.1 times higher than those in the Fatala River Basin.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…In comparison to the Fatala River Basin, these concentrations were approximately 25 times higher in Tehran in 2019 and 40 times higher in Arak in 2019. Comparing the data reported by Gharibvand et al [66] for Iranian cities in 2019 and 2020, it can be observed that ozone concentrations are 1.1 times higher than those in the Fatala River Basin.…”
Section: Discussionsupporting
confidence: 52%
“…This concentration of pollution is primarily linked to the historical development of the However, when comparing the concentrations of chemical substances obtained through Sentinel-5P satellite data within the Fatala River Basin to other global regions, it becomes evident that the quantified pollution levels are relatively low. For instance, Gharibvand et al [66] reported that in Tehran, Iran, the average concentration of nitrogen dioxide in 2019 was 523 µmol/m 2 , and in 2020, it was 505 µmol/m 2 . In Arak, Iran, the concentration was 710 µmol/m 2 in 2019 and 56 µmol/m 2 in 2020.…”
Section: Discussionmentioning
confidence: 99%
“…Risks and shocks, once they occur, will quickly spread along the urban network, resulting in cascading failures. For example, COVID-19 broke out at the end of 2019 and originated in the health sector but then quickly spread to the entire socio-economic network, causing the global economic recession since the 2008 financial crisis [5].…”
Section: Section 1: Introductionmentioning
confidence: 99%
“…For instance, on a global scale the Aura and Terra satellite of the National Aeronautics and Space Administration (NASA), and the GOSAT-2 satellites of Japan and China on a regional scale are are some of the satellites used to detect air pollution (Halder et al, 2023). Currently, the NASA Earth Observing System (EOS) satellite and its MODerate Resolution Imaging Spectroradiometer (MODIS) sensor, as well as the Sentinel-5 satellite from the European Space Agency's Copernicus project satellite series, are the preferred choices for air pollution studies (Gharibvand, Jamali, & Amiri, 2023;Nouri, Vahidi, Hatamzadeh, Afshinfar, & Karimi, 2023). These satellite systems can measure the levels of other greenhouse gases such as carbon monoxide, methane, and nitrogen dioxide.…”
Section: Introductionmentioning
confidence: 99%